Ruling Passions : Political Offices and Democratic Ethics - Sabl, Andrew, 1969- (Book collections on Project MUSE., 2002)
How should politicians act? When should they try to lead public opinion and when should they follow it? Should politicians see themselves as experts, whose opinions have greater authority than other people's, or as participants in a common dialogue with ordinary citizens? When do virtues like toleration and willingness to compromise deteriorate into moral weakness? In this innovative work, Andrew Sabl answers these questions by exploring what a democratic polity needs from its leaders. He concludes that there are systematic, principled reasons for the holders of divergent political offices or.